Learning to See. Short Essay on the Phenomenology of Understanding a Zen–Painting - Gelūnas, Arūnas (Acta Orientalia Vilnensia, 2000)
Article deals with the ways of appreciating calligraphy and ink–paintig – shodo and suibokuga – the East Asian trends of art heavily influenced by Zen. One of the central points in any discussion relating to Zen is whether the most profound level of communication is verbal or non–verbal. According to Shunrin Shuto, the spiritual teacher of a great Japanese suibokuga painter Sesshu, “A man who has only words is a Confucian [...].” Several aspects of Zen–verbalism are analysed with the quotations from various Oriental and Western authors.Almost every discourse on suibokuga starts with putting the particular painting or author in the historical perspective and the general context of the day, tracing back the influences and adding some notes on technical side of the work. lt is almost self–evident thing to present it in this way (at least to the non–Far–Eastern public). What could be better key to the best understanding of it?One of the usual and the most natural keys always present in China and Japan of the pre–ball–pen and precomputer era is the fact that every literate man had the mastery over the ink and the brush in a lesser or higher degree. So the first few seconds of observing the painting could reveal the direct and the spontaneous contents of the whole of the work even before one started recognising the details of the story or of the object depicted, this experience being based on the experience of the watching subject himself. The more trained the eye and the hand, the more adequate the feeling and the stronger the resonance.In this paper on the ways of experiencing an ink–painting, Miyamoto Musashi’s paintings being the example, the inevitable necessity of practice in the process of more profound understanding of this elegant and silent Art is demonstrated. The favourite metaphor the calligraphy teachers use in instructing the techniques of the brush – the brush in the hand of the painter or of the calligrapher being very similar to the sword in the hands of bushi – has led the author to the thought to try to draw the parallel between Miyamoto Musashi’s artwork and his “Book of the Five Rings” – the unsurpassed treatise on the sword–art.The article deals more with the paintings executed in so called “Haboku style of Yu–chien” than in more academic and careful manner of bunjinga of the Nothern Song or the paintings with inscriptions of the period of Ganzan Bungaku. Few comparisons with the Western art are given at the end.